Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ ÑÐ¾ÑÑ‚Ð°Ð²Ð° Ð·Ð°Ñ‰Ð¸Ñ‚Ð½Ñ‹Ñ… ÑÑ€ÐµÐ´ Ð¸ Ñ‚ÐµÐ¼Ð¿ÐµÑ€Ð°Ñ‚ÑƒÑ€Ñ‹ Ñ…Ñ€Ð°Ð½ÐµÐ½Ð¸Ñ Ð½Ð° ÑÐ¾Ñ…Ñ€Ð°Ð½Ð½Ð¾ÑÑ‚ÑŒ Ð»Ð¸Ð¾Ñ„Ð¸Ð»Ð¸Ð·Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ñ… Ð´Ñ€Ð¾Ð¶Ð¶ÐµÐ¹ Saccharomyces cerevisiae - Tsutsayeva, A. A.; Balyberdina, L. M.; Pavlenko, N. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
The effect of thiourea, as an antioxidant in cryoprotective medium under freeze-drying, on the baker’s yeast frozen-dried culture storage, was studied. Thiourea statistically and significantly increases their storage term in a viable state under 4° and -10°C. A number of viable cells and their properties remained unchanged under -25° and -75°C.